Detection of Signals with Chaotic Varying Forms and Low Intercept Probability - V. Р. Tuzlukov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2024)
Low probability of intercept performance of direct-sequence spread-spectrum system with chaotic spreading sequences is investigated. The energy detectors, synchronous and asynchronous, coherent and non-coherent structures are studied here to detect the presence of chaotic direct-sequence spread-spectrum signals. Simple detection approach using a binary correlation function to detect nonbinary chaotic sequences is proposed. The expressions of detection probabilities of chaotic spreading signals are derived. Comparisons between systems using chaotic and binary sequences are given in terms of the low probability of intercept performance, and the performance improvement with chaotic spreading sequences is observed.